1999
DOI: 10.1006/nimg.1998.0414
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Effective Cortical Connectivity in Vegetative State: Preliminary Investigation Using PET

Abstract: Vegetative state (VS) is a condition of abolished awareness with persistence of arousal. Awareness is part of consciousness, which itself is thought to represent an emergent property of cerebral neural networks. Our hypothesis was that part of the neural correlate underlying VS is an altered connectivity, especially between the associative cortices. We assessed regional cerebral glucose metabolism (rCMRGlu) and effective cortical connectivity in four patients in VS by means of statistical parametric mapping an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
228
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(253 citation statements)
references
References 24 publications
20
228
0
5
Order By: Relevance
“…TMS targets were selected bilaterally within the middle‐caudal portion of the superior frontal gyrus (BA6 and BA8) and within the superior parietal lobule (BA7), about 1cm lateral to the midline. These targets were chosen because they are part of a cortical network that has been suggested to be relevant for consciousness19, 20, 21 and because they are far from the insertion of head muscles that may induce TMS‐related artifacts 22. In brain‐injured patients, the stimulation of targets affected by cortical lesions identified on individual MR images was deliberately avoided because, in these cases, TMS is ineffective and does not evoke measureable responses 23.…”
Section: Methodsmentioning
confidence: 99%
“…TMS targets were selected bilaterally within the middle‐caudal portion of the superior frontal gyrus (BA6 and BA8) and within the superior parietal lobule (BA7), about 1cm lateral to the midline. These targets were chosen because they are part of a cortical network that has been suggested to be relevant for consciousness19, 20, 21 and because they are far from the insertion of head muscles that may induce TMS‐related artifacts 22. In brain‐injured patients, the stimulation of targets affected by cortical lesions identified on individual MR images was deliberately avoided because, in these cases, TMS is ineffective and does not evoke measureable responses 23.…”
Section: Methodsmentioning
confidence: 99%
“…Four regions of interest (ROIs) were localized on the canonical Montreal Neurological Institute (MNI) spatially normalized T1 weighted MRI image supplied by SPM2 based on the topography of our histologically identified areas (dPCC, vPCC, area 23d, RSC) using the MRIcro software package (Rorden & Brett, 2000). Mean normalized regional cerebral metabolic rates for glucose within each ROI were used for further functional connectivity assessment (i.e., metabolic cross-correlation studies) as described previously (Laureys et al, 1999). In brief, the entire brain volume was examined for clusters of voxels where metabolic activity correlated significantly with that measured in each of our histologically defined ROIs (dPCC, vPCC, area 23d, RSC).…”
Section: Regional Correlation Analysis In Resting Glucose Metabolismmentioning
confidence: 99%
“…Posterior cingulate and adjacent precuneal cortices were reported to show most impaired metabolism in UWS/VS (Laureys et al, 1999) and seem to differentiate MCS from UWS/VS patients (Laureys et al, 2004). More recently, a study on patients in the chronic stage of traumatic diffuse brain injury confirmed this bilateral frontoparietal hypometabolism and showed that these regions were more dysfunctional in UWS/VS than MCS patients (Nakayama et al, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…Cerebral metabolism was studied by means of FDG-PET after intravenous injection of 5-10 mCi of FDG on a Siemens CTI 951 R16/31 scanner as described elsewhere (Laureys et al, 1999(Laureys et al, , 2000a. Patients were monitored by two anesthesiologists 324 throughout the procedure.…”
Section: Fdg-petmentioning
confidence: 99%